Prenatal diagnosis and pregnancy outcomes of 1492 fetuses with congenital heart disease: role of multidisciplinary-joint consultation in prenatal diagnosis - Qiu, Xiuqing (Sci Rep, 2020)
Early diagnosis of congenital heart disease (CHD) can improve the prognosis of neonates with CHD. We retrospectively evaluated the value of prenatal diagnosis of CHD by comparing the pregnancy outcomes. Prenatal diagnosis of CHD was established by echocardiographic evaluation of fetal heart. Amniotic fluid and/or cord blood genetic examination, pathological anatomy, casting specimen, and/or multidisciplinary-joint consultation (MDJC) were performed. A total of 1492 fetuses with CHD were diagnosed by prenatal echocardiography from 67834 pregnant women. There were 445, 236, 583, and 228 cases in groups A (simple CHD), B (simple CHD plus extra-cardiac abnormality), C (complex CHD), and D (complex CHD plus extra-cardiac abnormality), respectively. The pregnancy continuation rate in the four groups was 98.67%, 85.71%, 67.65%, and 36.84%, respectively (P < 0.001). The pregnancy termination rate for fetal CHD with extra-cardiac abnormalities was significantly higher than that for fetuses with only CHD (81.24% vs. 53.6%, P < 0.05). Prenatal genetic test revealed chromosomal abnormalities in 20.43% of fetuses with CHD. MDJC significantly decreased the pregnancy termination rate. In 88 cases, the original decision to terminate the pregnancy was changed after consultation and the pregnancy was continued. Of these, 87 cases culminated in live births; 65 of these children had better prognosis. Nine-segment sequential segment analysis method for prenatal fetal echocardiography was compared with the results of pathological anatomy, cast specimen, postoperative diagnosis, and postnatal ultrasound. The accuracy of prenatal ultrasound for diagnosis of fetal complex CHD and fetal simple CHD was 90.5–91.66% and 98.6%, respectively. Prenatal ultrasound is still the most effective method for fetal CHD diagnosis.